Unlocking Reading Comprehension: The Power of the Reciprocal Teaching Method For EFL Learners - Kamarudin Kamarudin; Tri Setianingsih (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research aimed to examine the power of the Reciprocal Method on teaching reading comprehension to first-grade students at Senior High School SMAN 1 Batulayar during the 2025/2026 academic year. The study employed a pre-experimental design with pre-test and post-test assessments. The research involved all first-grade students in one class, consisting of 26 students. A reading test with 20 items was used as the instrument. The scores were analyzed using descriptive statistics, including mean, mode, median, and standard deviation, while inferential analysis was conducted to compare the t-test value with the t-table. The results revealed that the t-test value of 3.8962 was greater than the t-table value of 1.729. Based on these findings, the researcher concluded that the Reciprocal Method was effective to unlock reading comprehension among first-grade students at SMAN 1 Batulayar during the 2025/2026 academic year.